Dysbiotic Bacteria Translocate in Progressive SIV Infection - Klase, Zachary (Mucosal Immunol, 2015)
Infection of gut-resident CD4(+) memory T-cells during acute HIV and SIV infection is associated with rapid loss of these cells and damage to the epithelial barrier. Damage to the epithelial barrier allows translocation of microbial products from the intestinal lumen into the body. Immune activation caused by these microbial products has been associated with disease progression. Although microbial translocation has been demonstrated in SIV-infected nonhuman primates, the identity of translocating bacteria has not been determined. In this study we examined the communities of bacteria both within the GI tract and systemic tissues of both healthy and experimentally SIV-infected Asian macaques. While there were only modest changes in the GI tract-associated microbiome resulting from infection, there is substantial dysbiosis after administration of antiretrovirals. Analysis of bacterial DNA isolated from tissues of infected animals revealed a preference for the phylum Proteobacteria, suggesting that they preferentially translocate. Consistent with this finding, we observed increased metabolic activity of Proteobacterial species within the colonic lumen of SIV-infected animals. Overall these data provide insights into disease progression and suggest that therapies aimed at altering the composition and metabolic activity of the GI tract microbiome could benefit chronically-HIV infected individuals particularly those on antiretroviral therapies.